Globalization of Consumer Confidence - (:unkn) unknown (SAVEZ EKONOMISTA VOJVODINE, 2017)
The globalization of world economies and the importance of nowcasting analysis have been at the core of the recent literature. Nevertheless, these two strands of research are hardly coupled. This study aims to fill this gap through examining the globalization of the consumer confidence index (CCI) by applying conventional and unconventional econometric methods. The US CCI is used as the benchmark in tests of comovement among the CCIs of several developing and developed countries, with the data sets divided into three sub-periods: global liquidity abundance, the Great Recession, and post crisis. The existence and/or degree of globalization of the CCIs vary according to the period, whereas globalization in the form of coherence and similar paths is observed only during the Great Recession and, surprisingly, stronger in developing/emerging countries.
Keywords: Consumer confidence; Emerging markets; Advanced economies; Wavelet comovement analysis; COMOVEMENT